OYÍN ZAWÍQ QOSÍQLARÍ HÁM OLARDÍŃ JANRLÍQ ÓZGESHELIKLERI - Biysenbaev, Q. (SCIENCE and SOCIETY, 2023)
The article analyzes the characteristics and genre features of game songs as an independent genre. It was concluded that the features of this genre in children's folklore, such as age, performance, plot, game elements, and dramatic character, create an opportunity to study as an independent genre.